Sex Hormone Receptors in the Human Eye - Gupta, P.D.; Johar, Kaid; Nagpal, K.; Vasavada, A.R. (Survey of ophthalmology, 2005)
Dissimilarities in ocular physiopathology exist between human males and females. These differences can be observed in the lacrimal and other eye-associated glands, the ocular surface, the crystalline lens, and the retinochoroid complexes. Literature on the subject revealed that because of sex steroid hormone (estrogen, progesterone, and androgen) actions, various physiological conditions, such as age, menstrual cycles, pregnancy, and menopause or andropause, where the hormone milieu changes, affect vision. Well-designed scientific studies are lacking on the subject, although such studies hold much potential value. This review analyzes the relatively new area of hormones and vision.